Governance of public contracts: the materialization of efficiency and planning principles in law 14,133/2021 - Vivian Cristina Lima López Valle; João Pedro Teixeira Transmontano; Rodolfo Cancino Gómez (Sequência: Estudos Juridicos e Politicos, 2023)
This article seeks to elucidate the Governance of public contracts provided for in article 11, sole paragraph, of Law 14,133/2021, as the formalization of the efficiency and planning principles. Thus, it presents the historical search for professionalization, planning and efficiency in the Brazilian Public Administration, from the bureaucratic reform until the advent of the law 14,133/2021, with emphasis on the management reform from the 1990s. Afterwards, the subsequent approximation of private management mechanisms to public management is presented, with emphasis on corporate Governance, which, based on the agency theories, resulted in the concept of the organizational public Governance, based on the notions of leadership, strategy and control, widely present in the 2021 law through various instruments. The methodology used was that of bibliographic research.